Examining the performance of the alternative cut flower supply chains for smallholder producers in Da Lat using a pluralistic approach - Le, Bich Nhu (Curtin University, 2015)
This study examines the marketing margins; the gap between what each actor expected and what they received from upstream suppliers and downstream customers; and the nature of the relationships between exchange partners in Da Lat, Viet Nam. As prices were determined after the sale, farmers and market intermediaries preferred to transact with those exchange partners with whom they had developed a long-term relationship, and with whom there was a strong element of trust. Coercive market power was seldom exercised.